2013
DOI: 10.1093/mnras/stt752
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational lensing with f (χ) = χ3/2 gravity in accordance with astrophysical observations

Abstract: In this article we perform a second order perturbation analysis of the gravitational metric theory of gravity f (χ) = χ 3/2 developed by . We show that the theory accounts in detail for two observational facts: (1) the phenomenology of flattened rotation curves associated to the Tully-Fisher relation observed in spiral galaxies, and (2) the details of observations of gravitational lensing in galaxies and groups of galaxies, without the need of any dark matter. We show how all dynamical observations on flat rot… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
77
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(82 citation statements)
references
References 43 publications
5
77
0
Order By: Relevance
“…Small values of n yield soft transitions about the same point. For the case of spherically symmetric mass distribution, this extended Newtonian gravity approach proposal reproduces a MOND-like phenomenology [17] and has proven to be in good agreement with observations in astrophysical systems across different scales without invoking any dark matter component [4,5,8,9,14,15].…”
Section: Introductionsupporting
confidence: 69%
“…Small values of n yield soft transitions about the same point. For the case of spherically symmetric mass distribution, this extended Newtonian gravity approach proposal reproduces a MOND-like phenomenology [17] and has proven to be in good agreement with observations in astrophysical systems across different scales without invoking any dark matter component [4,5,8,9,14,15].…”
Section: Introductionsupporting
confidence: 69%
“…As pointed out by Mendoza et al [14], recent observations have shown that gravitational lensing on individual [15][16][17][18][19], groups [20] and clusters of galaxies [21,22] can be modelled with the standard Schwarzschild solution of general relativity, assuming the existence of a total dark plus baryonic isothermal halo, where the Tully-Fisher law holds for the baryonic matter. As such, the bending angle of light can be calculated using the standard lensing equation, finding that it does not depend on the impact parameter and scales with the square root of the total baryonic mass.…”
Section: Tully-fisher's Relativistic Correctionsmentioning
confidence: 99%
“…TeVeS of Bekenstein (2004), some of the F (R) theories, Capozziello & De Laurentis (2011), The extended Newtonian gravity of Mendoza et al (2011) or the covariant F (χ) of Mendoza et al (2013). For such theories, beyond a radius given by RM = (GM/a0) 1/2 , centrifugal equilibrium velocic 2015 RAS ties become flat at V = (GM a0) 1/4 .…”
Section: Introductionmentioning
confidence: 99%